2018
DOI: 10.3390/s18041301
|View full text |Cite
|
Sign up to set email alerts
|

Development and Hybrid Position/Force Control of a Dual-Drive Macro-Fiber-Composite Microgripper

Abstract: This paper reports on the development, implementation and hybrid control of a new micro-fiber-composite microgripper with synchronous position and force control capabilities. In particular, the micro-fiber-composite actuator was composed of rectangular piezoelectric fibers covered by interdigitated electrodes and embedded in structural epoxy. Thus, the micro-fiber-composite microgripper had a larger displacement-volume ratio (i.e., the ratio of the output displacement to the volume of the microgripper) than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…For sensing methods, sensing grippers are divided into the following: 1) Gripper sensing via external sensors. Zhang et al [2] reported a microgripper for position/force sensing using a laser displacement sensor. Rakotondrabe and Ivan [3] proposed a thermal-piezoelectric microgripper with an optical displacement sensor to measure the displacement.…”
Section: Introductionmentioning
confidence: 99%
“…For sensing methods, sensing grippers are divided into the following: 1) Gripper sensing via external sensors. Zhang et al [2] reported a microgripper for position/force sensing using a laser displacement sensor. Rakotondrabe and Ivan [3] proposed a thermal-piezoelectric microgripper with an optical displacement sensor to measure the displacement.…”
Section: Introductionmentioning
confidence: 99%
“…A selection of the A/D boards is not dependent on the kind of used piezoelectric material, so A/D boards are the same for the actuators based on PZT and actuators based on MFC. Control algorithms used for actuators based on PZT are also used for the actuators based on MFC: algorithms based on a linear function, e.g., PID [18], algorithms based on a state space, e.g., LQR [15], algorithms based on fuzzy functions, e.g., [19] and algorithms based on genetic methods, e.g., [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of microparts required by these technologies have complex threedimensional (3D) geometric structure and are made of different materials, and microassembly technology is also an important means to realize the manufacture of heterogeneous non-silicon microsystems [10]. Microgripper is end-effector of microassembly robot and is in direct contact with gripped microparts, so the research of microgripper is critical for microassembly technology and microassembly robot technology [11][12][13][14][15]. As a typical end-effector, microgrippers have good application prospect in the fields of micropart machining [16], microassembly [17] and bioengineering [18].…”
Section: Introductionmentioning
confidence: 99%